Understanding animal welfare : An integrated approach - Eadie, Edward N. (Animal Welfare, 2012)
This book examines the contents, influence, and potential of a personal selection of modern books published over the last fifty years that have been relevant to improving welfare. The works selected comprise three earlier classics that mainly deal with animal experimentation and intensive farming, as well as five that concentrate on specific subject areas, namely history, science, applied ethics, politics and law, that are important to protecting the welfare of animals against suffering inflicted by humans. The books are arranged in the order of their publication date, and for each one a few related works are also mentioned or discussed. This collection provides a broad understanding of animal protection issues, and provides the necessary basis for an informed and comprehensive approach to improving the welfare of animals. The books selected have been influential and they have the potential to improve animal welfare in the future.